Case Report: Nursing strategies for colon cancer surgery in third-trimester pregnancy - Zeng, Shiping; Chen, Jiayou; Luo, Yan; Song, Dan (Frontiers in Oncology, 2025)
BackgroundColorectal cancer during pregnancy is rare and poses significant challenges for maternal and fetal care. Postoperative nursing interventions are essential to optimize recovery and prevent complications.Case presentationA 33-year-old primigravida (G1P0) at 295 weeks’ gestation presented with abdominal distension, lower back pain, anorexia, and fatigue. Imaging and laboratory tests revealed right ascending colon wall thickening, hepatic lesions, fecal occult blood positivity, elevated AFP (162.4 IU/mL) and CA125 (64.5 U/mL), and severe anemia. She underwent cesarean section with right hemicolectomy, D3 lymph node dissection, and partial hepatectomy. Postoperative nursing care included pain management via patient-controlled analgesia, parenteral and oral nutrition, fluid and electrolyte monitoring, drainage tube care, early mobilization, fever surveillance, deep vein thrombosis prophylaxis, psychological support, and maternal-neonatal separation management.OutcomeThe patient recovered progressively without subjective complaints. No incision infection, vaginal fluid leakage, or mastitis occurred. The surgical incision healed with Grade A outcome, and she was discharged in stable condition.ConclusionThis case demonstrates the effectiveness of integrated, evidence-based postoperative nursing strategies in managing colorectal cancer during late pregnancy, providing guidance for similar complex cases.